Shallow subsurface fluid dynamics in the Malvinas Basin (SW Atlantic): A geoacoustic analysis - Ormazabal, Juan Pablo (2024)
Using a database consisting of sub-bottom profiles, 2D and 3D seismic data, a series of seep structures and acoustic anomalies associated with a plumbing system in the subsurface of the southern part of the Malvinas Basin off the Argentine coast are presented. The seep morphologies consist of mounds, pockmarks, and a carbonate mound, derived from hydrocarbons migrating from the Early Cretaceous Springhill and Lower Inoceramus formations through extensional faults and overthrusts of the Malvinas Fold-Thrust Belt and accumulating in the gas hydrate stability zone. This configuration is widely observed in the anticlines of the Malvinas Fold-Thrust Belt, which are characterized by a vertical structure highlighting a Bottom Simulating Reflector (BSR) overlain by a blanked-out zone at the seabed, interpreted as a gas hydrate stability zone. The plumbing system is influenced by active transtensional tectonics, as shown by two sets of extensional faults concentrated over some anticlines. These faults lead to displacements that, in many cases, reach the seabed. One nuance of the influence of tectonic activity on fluid escape is most evident in the Malvinas anticline, where all the pockmarks and the carbonate mound are concentrated. In the western part of the Malvinas anticline, five pockmarks are observed in an area characterized by a shallow BSR. In contrast, in the eastern part of the Malvinas Basin, one pockmark and one carbonate mound are derived from a series of extensional faults. The presented data, as well as a comparison between the western and eastern parts of the Malvinas anticline, indicate that the anticlines are the main cause of seepage in this area, as they allow the accumulation of migrating fluids. Likewise, the seepage morphologies outside the anticlines are much less pronounced, as can be observed in the mounds that overlie the bottom vents.